Full-biodegradable film and preparation method thereof
By using materials such as PLA, PBAT and modified calcium carbonate, PLA/PBAT/calcium carbonate composite materials are formed, which solves the problem of rigidity and toughness of biodegradable plastic films in high and low temperature environments, and achieves the effect of cost reduction and large-scale promotion.
Patent Information
- Application Number
- CN202311116289.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing biodegradable plastic films are rigid and tough in high and low temperature environments, which are difficult to achieve large-scale promotion, and are costly.
Using materials such as PLA, PBAT and calcium carbonate, modified calcium carbonate, modified PBAT and chain extender, PLA is modified to form a PLA/PBAT/calcium carbonate composite material, and the film is continuously blown by a single screw extruder.
It achieves good rigidity and toughness balance performance under high and low temperature environments, reduces production costs, and is suitable for large-scale promotion and use.
Smart Images

Figure BDA0004425279830000271 
Figure BDA0004425279830000281 
Figure BDA0004425279830000282
Abstract
Description
Technical Field
[0001] The invention belongs to the field of packaging films, and in particular relates to a fully biodegradable film and a preparation method thereof. Background Art
[0002] In recent years, the plastic industry has developed rapidly. While corresponding plastic products have brought great convenience to people's lives, a large amount of plastic waste has also brought huge environmental problems due to improper disposal. According to statistics, there are currently 120 million tons of disposable plastic products in the world, only 10% are recycled, another 12% are incinerated, and more than 70% are discarded into the soil, air and ocean.
[0003] To this end, the development of biodegradable plastics has become a hot topic and trend to completely solve white pollution. Biodegradable plastics refer to a type of plastic whose various properties meet the use requirements during the storage period and can be degraded into environmentally friendly substances under natural environmental conditions after use. Its standards are detailed in GB / T 41010-2021 "Degradability Performance and Labeling Requirements for Biodegradable Plastics and Products".
[0004] Biodegradable plastics have formed an industrial scale in the Chinese market, and polylactic acid (PLA) and polybutylene terephthalate-adipate (PBAT) occupy a large market share. PLA is mainly used for general plastics such as films, lunch boxes and other disposable products, while PBAT is mainly used in packaging, tableware and other fields. Polylactic acid has high tensile strength and elastic modulus (but it is brittle but not tough enough, its high-temperature mechanical properties are unstable, it is very sensitive to temperature changes, and its processing range is narrow. PBAT has good mechanical properties and toughness, high processing performance and thermal stability, but low strength.
[0005] At present, in order to meet the multiple quality indicators of biodegradable plastic films, polylactic acid PLA and PBAT are usually blended for film blowing. However, during the blow molding process, it was found that PLA and PBAT had poor compatibility and were difficult to blow mold continuously. Generally, compatibilizers were added to improve the compatibility and mechanical strength of the raw materials. Due to the high cost, the price of PLA / PBAT composite film is high, the market recognition is low, and it is difficult to promote it on a large scale. In addition, the biodegradable film blown by blending PLA and PBAT is highly sensitive to temperature and is greatly affected by the external environment. When the ambient temperature is high, the toughness of the film is enhanced and the strength is reduced. The rigidity and toughness of the prepared film are deteriorated. In the process of loading goods, it is easy to break the bag and leak items, which seriously affect the performance of the shopping bag. At the same time, the ambient temperature of its use is low, and the prepared shed film is not tough enough, brittle, easy to break, and difficult to use normally.
[0006] Chinese patent application CN100999587A discloses a fully degradable film with excellent heat resistance, non-anisotropic tear resistance and flexibility and a method for preparing the material thereof. The film composition is mainly composed of polylactic acid and aliphatic polyester and corresponding plasticizers and additives. From the perspective of the composition components, polylactic acid and aliphatic polyester cannot achieve good compatibility, and the obtained flexible film has poor heat resistance and puncture resistance. When used at high temperatures, the film is prone to creep deformation, affecting normal use.
[0007] Chinese patent application CN02801476.6 discloses a biodegradable resin polymer, film and agricultural film. The polymer is composed of fatty acid polyester and polylactic acid polymer, but the content of polylactic acid in the components is less than 20 parts of the total amount. The obtained film has the defects of low mechanical strength and poor tear resistance.
[0008] Chinese patent application CN104387732 A discloses a transparent tear-resistant polylactic acid biodegradable film and a preparation method thereof. The film is mainly composed of polylactic acid, a toughening agent, a plasticizer, a lubricant, and an opening agent. However, the polylactic acid film has poor toughness and is easily brittle. The added plasticizer is a small molecule substance and has the defect of easily overflowing from the polymer. In addition, the toughening agent polybutylene carbonate has poor thermal properties and is easily degraded during the processing process, resulting in reduced mechanical properties of the film, and poor puncture resistance and rigidity-toughness balance of the film.
[0009] Chinese patent application CN104893199 A discloses a fully degradable plastic film with a wide operating temperature range and strong toughness. The composition has many components and has the defects of poor compatibility and poor strength-toughness balance. The polyvinyl alcohol in the component is not specifically limited, and there is a defect of safety uncertainty.
[0010] Chinese patent application CN 105462124 A discloses a bio-based plastic and a preparation method thereof. The mixed solvent used in the application contains benzene substances, which are easily precipitated during the blow molding process and cannot meet the requirements of green processing technology.
[0011] Chinese patent application CN 106633722 A discloses a tear-resistant and high-toughness biodegradable material. The invention adopts a two-step method to prepare PBAT / nanomaterial one-step materials respectively; the reaction plasticization is completed in the front section of the extruder, and the reactive chain extension and capacity expansion are achieved in the middle and rear sections. The application has many components, requires specific extrusion equipment, and the cost of using additives is high. It is not suitable for large-scale promotion, and the puncture resistance of the film is not well presented.
[0012] Chinese patent application CN201611028759.6 discloses a tear-resistant and high-toughness biodegradable material and a preparation method thereof. The material is a PLA / PBAT binary alloy material. The tear resistance and toughness are mainly achieved through PBAT, plasticizers and other auxiliary materials. The toughness is greatly improved, but the tear resistance is not significantly improved, and the tensile strength is greatly reduced.
[0013] Chinese patent application CN201510646442.8 discloses a PLA / MMT degradation-enhanced masterbatch blended modified PLA / PBAT composite material and its preparation method. The application uses polylactic acid (PLA), poly(terephthalic acid-adipic acid-butylene glycol) copolyester (PBAT) and PLA / MMT degradation-enhanced masterbatch as raw materials, and evenly mixes 10-90 parts of PLA, 10-90 parts of PBAT, and 5-30 parts of PLA / MMT degradation-enhanced masterbatch, and melt-blends and modifies PLA / PBAT to prepare a PLA / PBAT composite material. The notched impact strength of the composite material is 5.30KJ / m 2 , the elongation at break is 16.23%. Therefore, the composite material is not suitable for packaging film, especially for express packaging film, because the elongation at break is far from the requirements of the application field and the versatility is poor.
[0014] Chinese patent application CN201510380483.7 discloses a method for preparing a PLA / PBAT / PPC composite modified material by reactive extrusion, wherein the components include PLA, PBAT, PPC, plasticizer, initiator, co-reactant, grafting monomer, and anti-aging additive. The toughness of the composite material is improved to a certain extent, but the tear resistance is not significantly improved, and due to the low tensile strength and poor heat resistance of PPC, the tensile strength of the composite material is lower than that of the PLA / PBAT binary composite material, and the heat resistance is also deteriorated.
[0015] Chinese patent application CN201310192664.8 discloses a PLA / PBAT biodegradable composite material, which is made of 60% to 75% by weight of polylactic acid, 60% to 75% of polybutylene adipate / terephthalate, 1% to 5% of polycaprolactone, 5% to 15% of ethylene-vinyl acetate copolymer, 1% to 5% of ethylene-vinyl acetate copolymer and polylactic acid graft copolymer, and 1% to 10% of vegetable oil polyol. Among them, ethylene-vinyl acetate copolymer is a petroleum-based material, does not have low-carbon environmental protection characteristics, and is not biodegradable in the natural environment, so the low-carbon biodegradability of the composite material is not good.
[0016] In summary, in view of the shortcomings of the existing technical means, the present invention provides a fully biodegradable film composition which is low in price, easy to shape and process, can be promoted on a large scale, and still has good rigidity-toughness balance performance under large changes in ambient temperature. Summary of the invention
[0017] The primary purpose of the present invention is to overcome the shortcomings and deficiencies in the above-mentioned prior art and to provide a low-cost, high-performance, fully biodegradable film and a preparation method thereof that can be promoted and used over a large area.
[0018] To this end, the present invention provides a fully biodegradable film, the raw materials of which include, by weight: 25 to 50 parts of PLA, 35 to 60 parts of PBAT, 15 to 30 parts of calcium carbonate, 0.2 to 0.6 parts of epoxy chain extender, and 0.2 to 1.0 parts of zinc stearate;
[0019] Wherein, the preparation method of the fully biodegradable film comprises:
[0020] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate;
[0021] (2) Mixing, melting and granulating activated calcium carbonate and PBAT to obtain a one-step modified material;
[0022] (3) melt blending the epoxy chain extender with PLA to obtain a two-step modified material;
[0023] (4) melt-blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material;
[0024] (5) The PLA / PBAT / calcium carbonate composite material is used to continuously blow into a film through a single screw extruder to obtain the fully biodegradable film.
[0025] The PLA is polylactic acid with a weight average molecular weight of 100,000 to 250,000, preferably polylactic acid with good moldability, wide processing range and a weight average molecular weight of 150,000 to 220,000.
[0026] The PBAT is polybutylene adipate / terephthalate with a weight average molecular weight of 50,000 to 100,000, preferably polybutylene adipate / terephthalate with a moderate molecular chain, a certain degree of branching, and a weight average molecular weight of 55,000 to 80,000.
[0027] The epoxy chain extender is a copolymer of one or more of cyclohexyl acrylate, glycidyl methacrylate, methyl methacrylate and styrene, preferably an epoxy chain extender capable of reducing the regularity of PLA and increasing the branching degree of PLA, containing 5 to 9 active epoxy groups, an epoxy equivalent of 300 to 400 g / mol, a particle size of 0.5 to 1.5 mm, and a weight average molecular weight of 7000 to 8000, such as BASF's ADR4468.
[0028] The zinc stearate is a common product in the market. The present invention preferably uses zinc stearate with low price and high market recognition, which is a white powder with a zinc content of 10-12% by mass, a free acid (calculated as stearic acid) of <0.5% by mass, and a particle size of 0.2-0.7 mm.
[0029] Wherein, the calcium carbonate is commercially available 700-1000 mesh heavy calcium carbonate, which is white in color.
[0030] The present invention also provides a method for preparing the above-mentioned fully biodegradable film, comprising:
[0031] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate;
[0032] (2) Mixing, melting and granulating activated calcium carbonate and PBAT to obtain a one-step modified material;
[0033] (3) melt blending the epoxy chain extender with PLA to obtain a two-step modified material;
[0034] (4) melt-blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material;
[0035] (5) The PLA / PBAT / calcium carbonate composite material is used to continuously blow into a film through a single screw extruder to obtain the fully biodegradable film.
[0036] Wherein, the step (1) further comprises:
[0037] (1.1) drying commercially available heavy calcium carbonate to obtain dried calcium carbonate, and then dispersing the dried calcium carbonate in an aqueous solution of ethylene glycol to obtain a suspension A of calcium carbonate;
[0038] (1.2) dissolving zinc stearate in an aqueous solution of ethylene glycol and dispersing the mixture to obtain a zinc stearate suspension B;
[0039] (1.3) The suspension A is further dispersed, and the suspension B is slowly added dropwise into the suspension A, and the dispersion is continued for a certain period of time, and then filtered, dried, and crushed to obtain the activated calcium carbonate.
[0040] The step (1.1) specifically comprises: placing commercially available heavy calcium carbonate in a vacuum oven at 75-90° C. and drying for 3-5 h (preferably 4 h), with a vacuum value of 0.05-0.15 MPa (preferably 0.10 MPa) to obtain dried calcium carbonate; then weighing 10-50 parts by weight of the dried calcium carbonate, placing it in an aqueous solution of 100-1000 parts by weight of ethylene glycol (wherein the volume ratio of ethylene glycol to deionized water is 80-90:10-20 (preferably 85:15)), and ultrasonically dispersing for 20-40 min (preferably 30 min) to obtain a suspension A of calcium carbonate.
[0041] The step (1.2) specifically comprises: dissolving 1 to 5 parts by weight of commercially available zinc stearate in 200 to 1000 parts by weight of an aqueous solution of ethylene glycol, and ultrasonically dispersing for 20 to 40 minutes (preferably 30 minutes) to obtain a suspension B of zinc stearate.
[0042] Wherein, in the step (1.3), the dispersion includes ultrasonic dispersion.
[0043] Wherein, in the step (1.3), after the suspension B is added dropwise into the suspension A, the dispersion is continued for a certain period of time, including: ultrasonic dispersion at 70-80° C. for 4-6 hours (preferably 5 hours) until the mixed solution is uniformly mixed.
[0044] Wherein, in the step (1), the particle size of the activated calcium carbonate obtained is 10-20 microns, and the content of zinc stearate in the activated calcium carbonate is 1.0-5.0% of the mass fraction of the activated calcium carbonate.
[0045] Wherein, the step (2) further comprises:
[0046] (2.1) Drying the activated calcium carbonate and PBAT particles to completely remove moisture and prevent hydrolysis, thereby obtaining dried activated calcium carbonate and dried PBAT particles;
[0047] (2.2) The dried activated calcium carbonate and the dried PBAT particles are stirred and mixed uniformly at a mass ratio of PBAT to activated calcium carbonate of 1.0 to 4.0, and then extruded and granulated to obtain the one-step modified material.
[0048] Wherein, in the step (2.1), the drying comprises: placing the activated calcium carbonate and PBAT particles in a vacuum drying oven at 60-80° C. (preferably 70° C.) for vacuum drying for 3-5 hours (preferably 4 hours).
[0049] Wherein, the step (2.2) specifically comprises: placing the dried activated calcium carbonate and the dried PBAT particles in a low-speed mixer and mixing them evenly, the stirring speed is 500-1000r / min, the stirring time is 10-15min, the stirring temperature is 10-20°C, and then extruding and granulating by a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52, and the granulation temperature is 130-150°C to achieve uniform dispersion of the modified calcium carbonate to obtain the one-step modified material.
[0050] Wherein, the step (3) further comprises:
[0051] (3.1) drying the epoxy chain extender and the PLA particles to obtain dried epoxy chain extender and dried PLA particles;
[0052] (3.2) The dried epoxy chain extender and the dried PLA particles are stirred and mixed uniformly at a ratio of 0.2-0.6% of the mass fraction of the PLA, and then extruded and granulated to obtain the two-step modified material.
[0053] Wherein, in the step (3.1), the drying comprises: placing the epoxy chain extender and PLA particles in a vacuum drying oven at 60-80° C. (preferably 70° C.) for vacuum drying for 3-5 hours (preferably 4 hours).
[0054] The step (3.2) specifically comprises: placing the dried epoxy chain extender and the dried PLA particles in a low-speed mixer and mixing them evenly, with a stirring speed of 500 to 1000 r / min, a stirring time of 10 to 15 min, and a stirring temperature of 10 to 20° C., and then extruding and granulating them using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48 to 52 at a granulation temperature of 150 to 170° C. to obtain the two-step modified material.
[0055] Wherein, the step (4) further comprises: mixing the first-step modified material and the second-step modified material in a low-speed mixer, the stirring speed is 500-1000 r / min, the stirring time is 5-10 min, the stirring temperature is 10-20° C., and extrusion granulation is performed using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52, and the granulation temperature is 150-170° C. to prepare a PLA / PBAT / calcium carbonate composite.
[0056] Wherein, the step (5) further comprises: placing the PLA / PBAT / calcium carbonate composite material in a vacuum drying oven at 60-80° C. (preferably 70° C.) for vacuum drying for 3-5 h (preferably 4 h), and continuously blowing it into a film through a single screw extruder with a length-to-diameter ratio of 20-30:1 (preferably 25:1), wherein the temperature of the extruder is 130-175° C., and air is introduced into the film bubble from the head of the blown film to inflate it, cool it, shape it through a herringbone plate, and tow it with a traction machine, and finally flatten and roll it with a winding device to obtain the fully biodegradable film.
[0057] Wherein, the thickness of the fully biodegradable film is 0.015-0.040 mm.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The present invention preferably uses excellent biodegradable materials PLA and PBAT as basic materials, epoxy chain extender, reinforcing filler calcium carbonate, and anti-aging agent zinc stearate as auxiliary components, wherein inexpensive calcium carbonate is used as a filler, and zinc stearate, a general plastic lubricant, is used. Innovative modification, production, and film-forming methods are used to prepare high-performance fully biodegradable films that can meet different needs.
[0060] (2) The high-performance fully biodegradable plastic film prepared by the present invention can effectively reduce the production cost while meeting the basic performance requirements of GB / T38082-2019 biodegradable plastic shopping bags, GB / T21661-2020 plastic shopping bags and GB_T 35795-2017 fully biodegradable agricultural ground covering films, and can use existing processing and molding technology to meet continuous blow molding production. The blown film has good scratch resistance and puncture resistance, can meet the requirements of high and low temperature use environments, and still has a good balance of rigidity and toughness under large temperature changes, and is easy to promote and use on a large scale.
[0061] (3) The method for preparing a high-performance fully biodegradable film of the present invention mainly comprises three steps of modification: calcium carbonate modified by zinc stearate, PBAT modified by modified calcium carbonate, and PLA modified by a chain extender; melt blending PBAT / modified calcium carbonate and PLA / chain extender to prepare a PLA / PBAT / calcium carbonate composite material; and finally using a general equipment single-screw extruder to blow a fully biodegradable film.
[0062] (4) The present invention fully utilizes the structural and performance advantages of each component, combines the strong components, improves the process preparation method, further exerts the synergistic effect between the components, and greatly improves the easy processing film-forming property, puncture resistance, tear resistance and strong and tough balance performance of PLA / PBAT film under high and low temperature environments.
[0063] (5) The present invention makes full use of the characteristics of calcium carbonate, such as physical reinforcement, strong chemical inertness, good thermal stability, low wear value, non-toxicity, odorlessness, health and environmental protection, and soil degradability. As a filler component of the degradable film composition, the present invention can effectively reduce the price cost of the film and is easy to promote and use on a large scale.
[0064] (6) The present invention uses zinc stearate, a general plastic modifier, to modify calcium carbonate and prepare hydrophobic active calcium carbonate. The polar groups of zinc stearate and the polar hydroxyl groups on the surface of calcium carbonate are tightly combined through hydrogen bonds or chemical bonds, and the non-polar groups of stearic acid are wrapped on the surface of calcium carbonate to form a coating, which effectively reduces the agglomeration between calcium carbonate particles.
[0065] (7) The present invention uses PBAT with a relatively low molecular weight and a high degree of branching. The terminal hydroxyl group and the terminal carboxyl group contained in PBAT are further combined with the polar group of the modified calcium carbonate. The non-polar chain of PBAT is combined with the stearic acid chain to achieve double-layer coating and dispersion of calcium carbonate, forming a "networked structure" in which the non-polar chain segments are entangled with each other, which is beneficial to further dispersion of calcium carbonate, and further improves the fluidity of the modified calcium carbonate.
[0066] (8) The above-mentioned double-layer coated "networked" calcium carbonate of the present invention is coated by organic active agent molecules with low surface tension, and its surface energy is reduced, the viscous resistance between particles is reduced, the flowability of particles is improved, and the particles have a similar flowability to liquid, and the particles have strong penetrating power. In the subsequent process of melt reaction extrusion granulation of the double-layer coated "Internet-type" PBAT / calcium carbonate and "highly branched" PLA / chain extender, the PBAT / calcium carbonate modified material can be inserted into the branched structure of PLA, forming a "branch-fruit" structure in which calcium carbonate is densely and evenly distributed as a whole, further increasing the contact area between the filler particles and the matrix resin, so that the filler particles can resist more impact when the film is impacted by external force, thereby improving the impact performance of the film. Furthermore, since the calcium carbonate particles are evenly distributed in the resin matrix, when subjected to external tearing force, the matrix ligaments around the particles will further yield, hindering the development of cracks, thereby improving the tear resistance of the film. At the same time, since the non-polar molecular chains are entangled with each other due to the melt shearing action, the modified calcium carbonate particles are evenly filled therein, so that the film still has excellent toughness, processing fluidity, dimensional stability and thermal stability when the external environment changes.
[0067] (9) The present invention selects a chain extender containing a specific active epoxy group to be melt-blended with PLA for modification. The epoxy group reacts with the hydroxyl and carboxyl groups on PLA to obtain a branched PLA structure with reduced regularity and increased branching degree, which is beneficial to the further penetration of fillers.
[0068] (10) The present invention fully utilizes the advantages of zinc stearate, calcium carbonate, chain extender, PBAT and PLA, and prepares the PLA / PBAT / calcium carbonate composite material by three-step modification of stearic acid-modified calcium carbonate, modified calcium carbonate-modified PBAT, and chain extender-modified PLA, two-step modification and granulation of PBAT-modified particles and PLA-modified particles, and finally melt blending. While fully mobilizing the advantages of each component and combining the strong components, the synergistic effect between the components is further exerted, and the puncture resistance and tear resistance of the PLA / PBAT film as well as the strong and tough balance performance under high and low temperature environments are greatly improved.
[0069] (11) The present invention uses a small number of raw materials. Through a general modification method, it combines the high mechanical strength and modulus of PLA, the high toughness and high and low temperature resistance of PBAT, the low price of calcium carbonate, the ability to be used as a reinforcing filler and the strong thermal stability, the "coupling" modification performance and anti-aging performance of zinc stearate, the performance of epoxy chain extender in improving the branching degree of PLA, the innovative preparation process and the appropriate ratio form a "branch-fruit" type reinforced network structure with uniform distribution of calcium carbonate, effectively reducing the production cost of the degradable plastic film composition and improving the performance and ease of promotion of the degradable plastic film. DETAILED DESCRIPTION
[0070] The present invention will be described in further detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only for illustration and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims of the present application.
[0071] In the following examples, the PLA was purchased from Natrueworks, USA; PBAT was purchased from Jinhui Zhaolong High-tech Co., Ltd.; the epoxy chain extender brand is ADR4468, purchased from BASF, and other raw materials and reagents, unless otherwise specified, are raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0072] Examples 1-5
[0073] Fully biodegradable films of Examples 1-5 were prepared. The composition ratios of the components of each example are shown in Table 1 below. The weight percentage of each component is shown in the table.
[0074] The activated calcium carbonate shown in Table 1 is specifically calcium carbonate modified with zinc stearate. In the subsequent tables, for example, 15 (1.0%) in Example 1 means that the weight proportion of activated calcium carbonate in the fully biodegradable film of Example 1 is 15%, and in the activated calcium carbonate, zinc stearate is 1.0% of the mass fraction of calcium carbonate; Examples 2-5 are similar.
[0075] Table 1 Raw materials and proportions of Examples 1-5 (by weight)
[0076] PLA PBAT Activated calcium carbonate Epoxy chain extender Example 1 25 60 15(1.0%) 0.05 Example 2 50 35 15(2.0%) 0.3 Example 3 35 35 30(3.0%) 0.14 Example 4 42 40 18(4.0%) 0.21 Example 5 38 39 22.5(5.0%) 0.11
[0077] The fully biodegradable films of Examples 1 to 5 above are prepared by the following method:
[0078] Example 1-According to the ratio shown in Table 1, the fully biodegradable film of Example 1 was prepared:
[0079] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0080] Commercially available heavy calcium carbonate was placed in a vacuum oven at 75°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 50 parts by weight of the dried calcium carbonate was weighed and placed in an aqueous solution of 1000 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0081] 3 parts by weight of commercially available zinc stearate were dissolved in 500 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0082] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 80° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 15 μm was prepared through filtration, drying and pulverization.
[0083] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0084] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 5000r / min, a stirring time of 15min, and a stirring temperature of 10°C, and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0085] (3) Melt blending of epoxy chain extender and PLA to obtain a two-step modified material:
[0086] The epoxy chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, and then placed in a low-speed mixer for uniform mixing. The stirring speed was 500 r / min, the stirring time was 10 min, and the stirring temperature was 10°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 48 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 150°C, 160°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender two-step modified material.
[0087] (4) Melting and blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material:
[0088] The PBAT / activated calcium carbonate one-step modified material and the PLA / chain extender two-step modified material were placed in a low-speed mixer and mixed evenly at a stirring speed of 800 r / min, a stirring time of 10 min, a stirring temperature of 20° C., and extruded by a twin-screw extruder with a length-to-diameter ratio (L / D) of 48. The granulation temperatures in zones 1-5 were 150° C., 150° C., 160° C., 165° C., and 170° C., respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0089] (5) Blow molding to obtain the fully biodegradable film:
[0090] The PLA / PBAT / calcium carbonate composite was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, and then blown into a film by a single-screw extruder, wherein the aspect ratio of the single-screw extruder was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head to inflate it, and the film was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled by a winding device to obtain a fully biodegradable film with a thickness of 0.030 mm.
[0091] Example 2-According to the ratio shown in Table 1, the fully biodegradable film of Example 2 was prepared:
[0092] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0093] Commercially available heavy calcium carbonate was placed in a vacuum oven at 90°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 30 parts by weight of the dried calcium carbonate were weighed and placed in an aqueous solution of 500 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0094] 2 parts by weight of commercially available zinc stearate were dissolved in 500 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0095] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 75° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 20 μm was prepared through filtration, drying and pulverization.
[0096] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0097] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 800r / min, a stirring time of 15min, and a stirring temperature of 15°C, and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0098] (3) Melt blending of epoxy chain extender and PLA to obtain a two-step modified material:
[0099] The epoxy chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, and then placed in a low-speed mixer for uniform mixing. The stirring speed was 1000 r / min, the stirring time was 10 min, and the stirring temperature was 15°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 150°C, 160°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender two-step modified material.
[0100] (4) Melting and blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material:
[0101] The PBAT / activated calcium carbonate one-step modified material and the PLA / chain extender two-step modified material were placed in a low-speed mixer and mixed evenly. The stirring speed was 500 r / min, the stirring time was 5 min, the stirring temperature was 10° C., and a twin-screw extruder with a length-to-diameter ratio (L / D) of 50 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150° C., 150° C., 160° C., 165° C., and 170° C., respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0102] (5) Blow molding to obtain the fully biodegradable film:
[0103] The PLA / PBAT / calcium carbonate composite was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, and then blown into a film by a single-screw extruder, wherein the aspect ratio of the single-screw extruder was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head to inflate it, and the film was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled by a winding device to obtain a fully biodegradable film with a thickness of 0.030 mm.
[0104] Example 3-According to the ratio shown in Table 1, the fully biodegradable film of Example 3 was prepared:
[0105] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0106] Commercially available heavy calcium carbonate was placed in a vacuum oven at 75°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 10 parts by weight of the dried calcium carbonate were weighed and placed in an aqueous solution of 100 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0107] 1 part by weight of commercially available zinc stearate was dissolved in 200 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension B of zinc stearate;
[0108] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 70° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 10 μm was prepared through filtration, drying and pulverization.
[0109] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0110] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 500r / min, a stirring time of 10min, and a stirring temperature of 10°C, and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 52, and the granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0111] (3) Melt blending of epoxy chain extender and PLA to obtain a two-step modified material:
[0112] The epoxy chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, and then placed in a low-speed mixer for uniform mixing. The stirring speed was 500 r / min, the stirring time was 5 min, and the stirring temperature was 10°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 150°C, 160°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender two-step modified material.
[0113] (4) Melting and blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material:
[0114] The PBAT / activated calcium carbonate one-step modified material and the PLA / chain extender two-step modified material were placed in a low-speed mixer and mixed evenly. The stirring speed was 500 r / min, the stirring time was 5 min, the stirring temperature was 10° C., and a twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150° C., 150° C., 160° C., 165° C., and 170° C., respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0115] (5) Blow molding to obtain the fully biodegradable film:
[0116] The PLA / PBAT / calcium carbonate composite was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, and then blown into a film by a single-screw extruder, wherein the aspect ratio of the single-screw extruder was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head to inflate it, and the film was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled by a winding device to obtain a fully biodegradable film with a thickness of 0.030 mm.
[0117] Example 4-According to the ratio shown in Table 1, the fully biodegradable film of Example 4 was prepared:
[0118] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0119] Commercially available heavy calcium carbonate was placed in a vacuum oven at 90°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 50 parts by weight of the dried calcium carbonate was weighed and placed in an aqueous solution of 1000 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0120] 5 parts by weight of commercially available zinc stearate were dissolved in 1000 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0121] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 80° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 15 μm was prepared through filtration, drying and pulverization.
[0122] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0123] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 800r / min, a stirring time of 15min, and a stirring temperature of 20°C, and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0124] (3) Melt blending of epoxy chain extender and PLA to obtain a two-step modified material:
[0125] The epoxy chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, and then placed in a low-speed mixer for uniform mixing. The stirring speed was 1000 r / min, the stirring time was 10 min, and the stirring temperature was 20°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 48 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 160°C, 165°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender two-step modified material.
[0126] (4) Melting and blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material:
[0127] The PBAT / activated calcium carbonate one-step modified material and the PLA / chain extender two-step modified material were placed in a low-speed mixer and mixed evenly at a stirring speed of 500 r / min, a stirring time of 10 min, and a stirring temperature of 20° C. The pelletization was performed by extrusion using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48. The pelletizing temperatures in zones 1-5 were 150° C., 160° C., 165° C., 165° C., and 170° C., respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0128] (5) Blow molding to obtain the fully biodegradable film:
[0129] The PLA / PBAT / calcium carbonate composite was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, and then blown into a film by a single-screw extruder, wherein the aspect ratio of the single-screw extruder was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head to inflate it, and the film was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled by a winding device to obtain a fully biodegradable film with a thickness of 0.030 mm.
[0130] Example 5-According to the ratio shown in Table 1, the fully biodegradable film of Example 5 was prepared:
[0131] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0132] Commercially available heavy calcium carbonate was placed in a vacuum oven at 85°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 40 parts by weight of the dried calcium carbonate was weighed and placed in an aqueous solution of 800 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0133] 3 parts by weight of commercially available zinc stearate were dissolved in 750 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0134] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 75° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 15 μm was prepared through filtration, drying and pulverization.
[0135] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0136] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70° C. for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 800 r / min, a stirring time of 12 min, and a stirring temperature of 12° C., and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 130° C., 130° C., 140° C., 145° C., and 150° C., respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0137] (3) Melt blending of epoxy chain extender and PLA to obtain a two-step modified material:
[0138] The epoxy chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, and then placed in a low-speed mixer for uniform mixing. The stirring speed was 800 r / min, the stirring time was 8 min, and the stirring temperature was 12°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 160°C, 165°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender two-step modified material.
[0139] (4) Melting and blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material:
[0140] The PBAT / activated calcium carbonate one-step modified material and the PLA / chain extender two-step modified material were placed in a low-speed mixer and mixed evenly. The stirring speed was 800 r / min, the stirring time was 8 min, the stirring temperature was 12 ° C, and a twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150 ° C, 160 ° C, 165 ° C, 165 ° C, and 170 ° C, respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0141] (5) Blow molding to obtain the fully biodegradable film:
[0142] The PLA / PBAT / calcium carbonate composite was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, and then blown into a film by a single-screw extruder, wherein the aspect ratio of the single-screw extruder was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head to inflate it, and the film was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled by a winding device to obtain a fully biodegradable film with a thickness of 0.030 mm.
[0143] Comparative Example 1:
[0144] Chinese patent application CN 106633722 A discloses a tear-resistant and high-toughness biodegradable material and a preparation method thereof. Example 6 in the specification of CN 106633722 A is used as comparative example 1 of the present invention.
[0145] Specific implementation method: accurately weigh 95 kg of carbon nanotubes CNTS-5, heat to 80° C. with a high-speed mixer, mix at high speed and add 5 kg of KH-560 in a spraying manner, mix for 20 minutes, and obtain surface-treated nano carbon nanotubes CNTS-5.
[0146] Accurately weigh 10 kg of the surface-treated nanocarbon CNTS-5 and 90 kg of PBAT TH801, use an internal mixer at 160 ° C and a rotation speed of 40 rpm for 10 minutes, and then use a single screw extruder with a length-to-diameter ratio of 40:1 for melt mixing, the extrusion temperature is 170 ° C, and the screw speed is 800 rpm to obtain PBAT / CNTS-5 one-step material.
[0147] Accurately weigh 40 kg of PLA 101, 30 kg of PBAT / CNTS-5 one-step material, 15 kg of acetyl epoxidized vegetable oil acid adipyl glyceride, 14.4 kg of talc, 0.1 kg of epoxy chain extender 4370, and 0.5 kg of antioxidant 1076.
[0148] The above components are pre-mixed evenly, and melt-kneaded using a twin-screw extruder. The temperatures of the heating zones of the extruder from the feed port to the die are set to 130°C, 180°C, 180°C, 180°C, 180°C, and 180°C, respectively, with a rotation speed of 200 rpm to obtain a tear-resistant and high-toughness biodegradable material.
[0149] The tear-resistant and high-toughness biodegradable material was placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and extruded through a single screw extruder with a length-to-diameter ratio of 25:1, a screw speed of 80 r / min, and an extrusion temperature of 165°C. Air was introduced into the film bubble from the head to inflate it, and the film bubble was cooled, shaped by a herringbone plate, and towed by a traction machine. Finally, it was flattened and rolled up by a winding device to obtain a 30 μm thick biodegradable film of Comparative Example 1.
[0150] Comparative Example 2:
[0151] Chinese patent application CN 109486138 A discloses a PHA-modified PLA / PBAT biodegradable resin and a preparation method thereof. Example 3 in the specification of CN 109486138 A is used as Comparative Example 2 of the present invention.
[0152] Specific implementation method: PHA modified PLA / PBAT biodegradable resin is prepared from the following raw materials in parts by weight: 35 parts of PLA, 35 parts of PBAT, and 30 parts of PHA. The resin is formed into a film by a film blowing machine to obtain a 30 μm thick biodegradable film of Comparative Example 2.
[0153] Comparative Example 3:
[0154] Comparative Example 3 is substantially the same as Example 3, except that activated calcium carbonate is melt-blended with PLA, chain extender, and PBAT in one step. The specific preparation method of Comparative Example 3 is as follows:
[0155] Weigh each raw material according to the formula of Example 3 shown in Table 1,
[0156] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0157] Commercially available heavy calcium carbonate was placed in a vacuum oven at 75°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 10 parts by weight of the dried calcium carbonate were weighed and placed in an aqueous solution of 100 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0158] 1 part by weight of commercially available zinc stearate was dissolved in 200 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension B of zinc stearate;
[0159] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 80° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 20 μm was prepared through filtration, drying and pulverization.
[0160] (2) One-step melt blending and extrusion modification to prepare PLA / PBAT / calcium carbonate composites:
[0161] The activated calcium carbonate, epoxy chain extender, PLA particles, and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis. The activated calcium carbonate, epoxy chain extender, PLA particles, and PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 1000r / min, a stirring time of 15min, and a stirring temperature of 20°C. Then, a twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate and obtain a PLA / PBAT / calcium carbonate composite.
[0162] (3) Blow molding to obtain biodegradable film
[0163] The PLA / PBAT / calcium carbonate composite material prepared above was placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and blown into a film by a single screw extruder. The aspect ratio was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head of the die to inflate it, cool it, shape it through a herringbone plate, and pull it with a traction machine. Finally, it was flattened and rolled up by a winding device to obtain a 30 μm thick biodegradable film of Comparative Example 3.
[0164] Comparative Example 4
[0165] Comparative Example 4 is substantially the same as Example 4, except that in Comparative Example 4, activated calcium carbonate is directly melt-blended with a chain extender and PLA. The preparation method of Comparative Example 4 is as follows:
[0166] Weigh each raw material according to the formula of Example 4 shown in Table 1,
[0167] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0168] Commercially available heavy calcium carbonate was placed in a vacuum oven at 90°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 50 parts by weight of the dried calcium carbonate was weighed and placed in an aqueous solution of 1000 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0169] 5 parts by weight of commercially available zinc stearate were dissolved in 1000 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0170] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 80° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 15 μm was prepared through filtration, drying and pulverization.
[0171] (2) Active calcium carbonate and PBAT are mixed, melted, and granulated to obtain a one-step modified material:
[0172] The activated calcium carbonate and PBAT particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours to completely remove moisture and prevent hydrolysis; the dried activated calcium carbonate and dried PBAT particles were placed in a low-speed mixer and mixed evenly, with a stirring speed of 800r / min, a stirring time of 15min, and a stirring temperature of 20°C, and then extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 130°C, 130°C, 140°C, 145°C, and 150°C, respectively, to achieve uniform dispersion of the activated calcium carbonate, and to obtain a PBAT / activated calcium carbonate one-step modified material.
[0173] (3) Preparation of PLA / PBAT / calcium carbonate composites by two-step melt blending and extrusion:
[0174] The PBAT / activated calcium carbonate one-step modified material, PLA particles, and epoxy chain extender were placed in a low-speed mixer and mixed evenly at a stirring speed of 1000 r / min, a stirring time of 10 min, and a stirring temperature of 20° C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48. The granulation temperatures in zones 1-5 were 160° C., 160° C., 165° C., 165° C., and 170° C., respectively, to obtain a PLA / PBAT / calcium carbonate composite.
[0175] (3) Blow molding to obtain biodegradable film
[0176] The PLA / PBAT / calcium carbonate composite material prepared above was placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and blown into a film by a single screw extruder. The aspect ratio was 25:1, and the blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head of the blown film to inflate it, cool it, shape it through a herringbone plate, and pull it with a traction machine. Finally, it was flattened and rolled up by a winding device to obtain a 30 μm thick biodegradable film of Comparative Example 4.
[0177] Comparative Example 5
[0178] Comparative Example 5 is substantially the same as Example 5, except that in Comparative Example 5, activated calcium carbonate, PBAT particles, and PLA / chain extender modified particles are melt blended. The preparation method of Comparative Example 5 is as follows:
[0179] Weigh each raw material according to the formula of Example 5 shown in Table 1,
[0180] (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate:
[0181] Commercially available heavy calcium carbonate was placed in a vacuum oven at 85°C and dried for 4 hours, with a vacuum value of 0.05 MPa. 40 parts by weight of the dried calcium carbonate was weighed and placed in an aqueous solution of 800 parts by weight of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and the mixed solution was ultrasonically dispersed for 30 minutes to obtain a suspension A of calcium carbonate;
[0182] 3 parts by weight of commercially available zinc stearate were dissolved in 750 parts by weight of an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a zinc stearate suspension B;
[0183] The suspension A was further ultrasonically dispersed, and the suspension B was slowly added dropwise to the suspension A, and ultrasonically dispersed at 75° C. for 5 hours until the mixture was uniformly mixed. The activated calcium carbonate with a particle size of 15 μm was prepared through filtration, drying and pulverization.
[0184] (2) Preparation of PLA / PBAT / calcium carbonate composites by two-step melt blending and extrusion modification:
[0185] The chain extender and PLA particles were vacuum dried in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer at a stirring speed of 800 r / min, a stirring time of 12 min, and a stirring temperature of 12°C. The particles were extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50. The granulation temperatures in zones 1-5 were 150°C, 150°C, 160°C, 165°C, and 170°C, respectively, to obtain a PLA / chain extender modified material.
[0186] Activated calcium carbonate, PBAT particles, and PLA / chain extender modified materials were placed in a low-speed mixer and mixed evenly at a stirring speed of 800 r / min, a stirring time of 8 min, and a stirring temperature of 12°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 52 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 160°C, 160°C, 165°C, 165°C, and 170°C, respectively, to prepare a PLA / PBAT / calcium carbonate composite.
[0187] (3) Blow molding to obtain biodegradable film
[0188] The PLA / PBAT / calcium carbonate composite material prepared above was placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and blown into a film by a single screw extruder. The aspect ratio was 25:1, and the film blowing temperatures in zones 1-5 were 130°C, 140°C, 160°C, 165°C, and 175°C, respectively. Air was introduced into the film bubble from the head of the die to inflate it, cool it, shape it through a herringbone plate, and pull it with a traction machine. Finally, it was flattened and rolled up by a winding device to obtain a 30 μm thick biodegradable film of Comparative Example 5.
[0189] Comparative Example 6:
[0190] A biodegradable plastic film of a famous brand on the market with a thickness of 30 μm was purchased as Comparative Example 6.
[0191] Performance effect test:
[0192] The biodegradable plastic films prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were subjected to performance tests. The specific test methods are as follows:
[0193] The tensile strength, tensile yield stress and nominal strain at break are tested according to GB / T1040.3-2006, and the tensile rate is 200 mm / min.
[0194] Elmendorf tear strength: tested in accordance with GB / T 16578.2~2009, using rectangular specimens.
[0195] Puncture performance test: Cut the membrane into a circle with a diameter of 2.5 cm, stretch it on the mouth of a small triangular bottle, and use INSTRON to measure the pressure that the membrane can withstand, expressed as the maximum pressure per unit cross-sectional area (N / mm 2 ). The drill diameter is 13mm and the descending speed is 50mm / min.
[0196] Dart mass impact test: The dart mass impact test is carried out in accordance with the provisions of GB / T9639.1~2008A, using a single specimen, not the step method, and a method of determining the number of undamaged samples using a fixed dart mass. The dart mass is 50g and the number of samples is 10.
[0197] Heat resistance test: overlap two surfaces, apply a load of 4.9N on them, put them in an oven at 80℃ for 1 hour, take them out and immediately separate the two overlapping samples to check whether there are any abnormal conditions such as adhesion and melting marks on the surface.
[0198] Cold resistance test: Take 4 samples from the test film or bag, about 300mm long and 20mm wide. Put the other two samples in a constant temperature box at 22℃ for more than 2 hours, take out the samples and fold them 180° in the length direction to check whether there are any abnormalities such as damage and cracks on the film surface.
[0199] Lifting test: Bag fatigue testing machine, amplitude 30mm±2mm, frequency 2~3Hz, put simulant (such as sand, rice grains, etc.) equivalent to the nominal load and with a volume not exceeding two-thirds of the effective solvent in the bag into the bag, and then hang it on the testing machine. Test 1800 times, observe the bag body and the bag for damage, and test 3 times.
[0200] Drop test: put a simulant (such as sand, rice grains, etc.) equivalent to the nominal weight and with a volume not exceeding two-thirds of the effective volume of the bag into the bag, remove the remaining air, seal the bag mouth with adhesive tape while keeping the upper bag film fully relaxed, and let the bag fall freely from a height of 0.5m above the bottom of the bag. The test ground should be a smooth, flat and hard ground, and observe whether the simulant (such as sand, rice grains, etc.) leaks out. The number of tests is 3.
[0201] The fully biodegradable films prepared in Examples 1-5 meet the requirements of GB / T38082-2019 and GB / T21661-2020. Other performance results are shown in Table 2.
[0202] The test results of Comparative Examples 1-6 are shown in Table 3.
[0203] Table 2 Performance test results of Examples 1-5
[0204]
[0205]
[0206] Table 3 Performance test results of comparative examples 1-6
[0207]
[0208]
[0209] By comparing the test results of the embodiment and the comparative example, it can be seen that the standard test thickness of the biodegradable plastic film is 30 μm, and under the same test conditions:
[0210] (1) Comparative Example 1 is an example in CN 106633722 A. The carbon nanotubes are pretreated by the same method as in CN 106633722 A, and qualified special materials for degradable materials are prepared by two-step melt mixing. Then, a biodegradable plastic film is prepared by a blown film process consistent with the present invention. Although the obtained film has high tear strength and toughness, it has more added components and poor puncture ability. There are cracks in the cold resistance test, and there are damages in the drop test and the lifting test.
[0211] (2) Comparative Example 2 is an example in CN 109486138 A. The same method as CN 109486138 A is used to prepare a biodegradable plastic film. The raw material components are relatively simple, but: PHA is relatively expensive and has a low degree of commercialization. In addition, PHA has low toughness, increased brittleness, poor puncture resistance, and fails the dart impact test. The prepared degradable plastic film is relatively sensitive to changes in external temperature and fails both the cold resistance test and the heat resistance test.
[0212] (3) In Comparative Example 3, all raw materials were directly melt-blended in one step, and the overall mechanical properties of the plastic bag were significantly reduced, the compatibility between the raw material components was reduced, the puncture resistance was poor, and the cold resistance test, lifting test, and drop test were all unqualified;
[0213] (4) Comparative Example 4 uses PLA that has not been modified with a chain extender, and directly melt-blends the PBAT / calcium carbonate one-step modified material with a chain extender and PLA, and granulates the mixture to prepare a degradable film. Although this improves the overall mechanical properties of the film to a certain extent, PLA does not form a strong branched structure, and the dispersibility of the filler calcium carbonate is much worse than that of Example 4, resulting in failures in the dart drop test, the lifting test, and the drop test;
[0214] (5) In Comparative Example 5, the modified calcium carbonate was not first blended and modified with PBAT, which reduced the further dispersion of the modified calcium carbonate, failed to effectively utilize the short chain and branched structure of PBAT, and the calcium carbonate could not be effectively inserted into the extended chain structure of PLA. The formed filler structure was not as uniform and neat as that of Example 5, resulting in the overall performance of the prepared film being worse than that of Example 5, and the dart drop test, cold resistance test, lifting test, and drop test were all unqualified;
[0215] (6) Comparative Example 6 is a biodegradable plastic film of a certain brand purchased, which has good mechanical properties. However, it is consistent with the actual use in the market. It is easy to be damaged when encountering hard objects. The overall puncture resistance of the film is poor. In addition, the heat resistance test, cold resistance test, lifting test and drop test are all unqualified;
[0216] (7) The embodiments of the present invention make full use of the physical enhancement, strong chemical inertness, good thermal stability, low wear value, non-toxicity, odorlessness, health, environmental protection and soil degradability of calcium carbonate. As a filler component of the degradable film composition, it can effectively reduce the price cost of the film and is easy to promote and use on a large scale.
[0217] The invention adopts zinc stearate, a general plastic modifier, to modify calcium carbonate and prepare hydrophobic active calcium carbonate. The polar groups of zinc stearate and the polar hydroxyl groups on the surface of calcium carbonate are tightly combined through hydrogen bonds or chemical bonds, and the non-polar groups of stearic acid are wrapped on the surface of calcium carbonate to form a coating, which effectively reduces the agglomeration between calcium carbonate particles.
[0218] The present invention selects PBAT with a low molecular weight and a high degree of branching. The terminal hydroxyl group and the terminal carboxyl group contained in PBAT are further combined with the polar group of the modified calcium carbonate, and the non-polar chain of PBAT is combined with the stearic acid chain to achieve double-layer coating and dispersion of calcium carbonate, forming a "networked structure" in which the non-polar chain segments are entangled with each other, which is beneficial to further dispersion of calcium carbonate, and further improves the fluidity of the modified calcium carbonate.
[0219] The present invention selects a chain extender containing a specific active epoxy group to be melt-blended with PLA for modification, and the epoxy group reacts with the hydroxyl group and the carboxyl group on the PLA to obtain a branched PLA structure with reduced regularity and increased branching degree, which is beneficial to further penetrating addition of fillers.
[0220] The double-layer coated "networked" calcium carbonate of the present invention is coated by organic active agent molecules with low surface tension, and its surface energy is reduced, the viscous resistance between particles is reduced, the flow performance of particles is improved, and the particles have a flowability similar to that of liquid, and the particles have strong penetrating power. The double-layer coated "internet-type" PBAT / calcium carbonate and the "highly branched" PLA / chain extender are melt-reacted and extruded to granulate, and the PBAT / calcium carbonate modified material can be inserted into the branched structure of PLA, forming a "branch-fruit" structure in which calcium carbonate is densely and evenly distributed as a whole, further increasing the contact area between the filler particles and the matrix resin, and the filler particles can resist more impact forces when the film is impacted by external forces, thereby improving the impact performance of the film. Due to the presence of calcium carbonate particles, when subjected to tearing force, the matrix ligaments around the particles will further yield, hindering the development of cracks, thereby improving the tear resistance of the film. The non-polar molecular chains are entangled with each other under the action of melt shear, and the modified calcium carbonate particles are uniformly filled therein, so that the film still has excellent toughness, processing fluidity, dimensional stability and thermal stability when the external environment changes.
[0221] The invention fully combines the advantages of various raw materials, combines the high mechanical strength and modulus of PLA, the high toughness and high and low temperature resistance of PBAT, the low price of calcium carbonate, the ability to be used as a reinforcing filler and the strong thermal stability, the "coupling" modification performance and anti-aging performance of zinc stearate, the performance of epoxy chain extender in improving the branching degree of PLA, the three-step modified preparation process, and the appropriate component ratio to form a "branch-fruit" type reinforced network structure with uniform distribution of calcium carbonate, effectively reducing the production cost of the degradable plastic film composition, greatly improving the puncture resistance and tear resistance of the PLA / PBAT film, and still having good strength-toughness balance performance under high and low temperature environments, further improving the use performance and ease of promotion of the degradable plastic film.
[0222] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0223] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0224] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A fully biodegradable film, the raw materials of which include, by weight: 25-50 parts of PLA, 35-60 parts of PBAT, 15-30 parts of calcium carbonate, 0.05-0.25 parts of epoxy chain extender, 0.2-1.2 parts of zinc stearate; Wherein, the preparation method of the fully biodegradable film comprises: (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate; (2) Mixing, melting and granulating activated calcium carbonate and PBAT to obtain a one-step modified material; (3) melt blending the epoxy chain extender with PLA to obtain a two-step modified material; (4) melt-blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material; (5) The PLA / PBAT / calcium carbonate composite material is used to continuously blow into a film through a single screw extruder to obtain the fully biodegradable film.
2. The fully biodegradable film according to claim 1, wherein: The PLA is polylactic acid with a weight average molecular weight of 100,000 to 250,000, and the PBAT is polybutylene adipate / terephthalate with a weight average molecular weight of 50,000 to 100,000, preferably polybutylene adipate / terephthalate with a moderate molecular chain, a certain degree of branching, and a weight average molecular weight of 55,000 to 80,000.
3. The fully biodegradable film according to claim 1, wherein: The epoxy chain extender is a copolymer of one or more of cyclohexyl acrylate, glycidyl methacrylate, methyl methacrylate and styrene.
4. The fully biodegradable film according to claim 1, wherein: The thickness of the fully biodegradable film is 0.015-0.040 mm.
5. The method for preparing a fully biodegradable film according to any one of claims 1 to 4, comprising: (1) Modifying calcium carbonate with zinc stearate to obtain active calcium carbonate; (2) Mixing, melting and granulating activated calcium carbonate and PBAT to obtain a one-step modified material; (3) melt blending the epoxy chain extender with PLA to obtain a two-step modified material; (4) melt-blending the first-step modified material and the second-step modified material to obtain a PLA / PBAT / calcium carbonate composite material; (5) The PLA / PBAT / calcium carbonate composite material is used to continuously blow into a film through a single screw extruder to obtain the fully biodegradable film.
6. The method for preparing a fully biodegradable film according to claim 5, wherein: The step (1) comprises: (1.1) drying commercially available heavy calcium carbonate to obtain dried calcium carbonate, and then dispersing the dried calcium carbonate in an aqueous solution of ethylene glycol to obtain a suspension A of calcium carbonate; (1.2) dissolving zinc stearate in an aqueous solution of ethylene glycol and dispersing the mixture to obtain a zinc stearate suspension B; (1.3) The suspension A is further dispersed, and the suspension B is slowly added dropwise into the suspension A, and the dispersion is continued for a certain period of time, followed by suction filtration, drying, and pulverization to obtain the activated calcium carbonate.
7. The method for preparing a fully biodegradable film according to claim 5, wherein: The step (2) comprises: (2.1) drying the activated calcium carbonate and PBAT particles to obtain dried activated calcium carbonate and dried PBAT particles; (2.2) The dried activated calcium carbonate and the dried PBAT particles are stirred and mixed uniformly at a mass ratio of PBAT to activated calcium carbonate of 1.0 to 4.0, and then extruded and granulated to obtain the one-step modified material.
8. The method for preparing a fully biodegradable film according to claim 5, wherein: The step (3) comprises: (3.1) drying the epoxy chain extender and the PLA particles to obtain dried epoxy chain extender and dried PLA particles; (3.2) The dried epoxy chain extender and the dried PLA particles are stirred and mixed uniformly at a ratio of 0.2-0.6% of the mass fraction of the PLA, and then extruded and granulated to obtain the two-step modified material.
9. The method for preparing a fully biodegradable film according to claim 5, wherein: The step (4) comprises: uniformly mixing the first-step modified material and the second-step modified material in a low-speed mixer, and extruding and granulating them using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48 to 52 at a granulation temperature of 150 to 170° C. to prepare a PLA / PBAT / calcium carbonate composite material.
10. The method for preparing a fully biodegradable film according to claim 5, wherein: The step (5) comprises: vacuum drying the PLA / PBAT / calcium carbonate composite material, and continuously blowing it into a film through a single screw extruder with a length-to-diameter ratio of 20-30:1, wherein the extruder temperature is 130-175° C., to obtain the fully biodegradable film.
Citation Information
Patent Citations
Biological whole degrading film and mfg. process of its material
CN100999587A
PLA / PBAT biodegradable composite material and preparation method thereof
CN103254597A
Transparent, tear-resistant and biodegradable polylactic acid thin film and preparation method thereof
CN104387732A
Full-degradable plastic film with wide using temperature range and strong toughness and manufacturing method thereof
CN104893199A
Method for preparing PLA / PBAT / PPC composite modified material through reactive extrusion
CN105038083A
Cited By
Antibacterial degradable packaging film and preparation method thereof
CN120574468A
A reinforced and toughened polylactic acid composite prepared from a bio-based modified calcium carbonate powder and a preparation method thereof
CN122647871A